2009
DOI: 10.1111/j.1471-0528.2009.02185.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor polymorphisms and the risk of endometrial cancer

Abstract: Objective There is evidence that estrogens and some of their metabolites are involved in endometrial cancer pathogenesis. As estrogens mediate their effects via the estrogen receptors, ESR1 and ESR2, the objective of this investigation was to determine whether six single nucleotide polymorphisms (SNPs) in these two genes were over-represented in a population of endometrial cancer patients compared with a healthy matched control population, thereby associating differences in these genes with endometrial cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 17 publications
4
26
0
Order By: Relevance
“…The study population has been described previously [19][20][21][22]. Briefly, the initial population consisted of 451 consecutive Caucasian women who were registered at the Hunter Centre for Gynaecological Cancer, John Hunter Hospital, Newcastle, New South Wales, Australia between the years 1992 and 2005.…”
Section: Study Populationmentioning
confidence: 99%
“…The study population has been described previously [19][20][21][22]. Briefly, the initial population consisted of 451 consecutive Caucasian women who were registered at the Hunter Centre for Gynaecological Cancer, John Hunter Hospital, Newcastle, New South Wales, Australia between the years 1992 and 2005.…”
Section: Study Populationmentioning
confidence: 99%
“…From a meta-analysis conducted by Ioannidis et al have found that for women who were homozygous for the absence of an XbaI recognition site, the adjusted odds of all fractures were reduced by 19% (OR = 0.81, 95% CI = 0.71-0.93) and vertebral fractures by 35% (OR = 0.65, 95% CI = 0.49-0.87) (Ioannidis et al, 2004). Wedren et al found that allele C was associated with a significant reduced risk for endometrial cancer risk (Wedren et al, 2008), but another study conducted by Ashton et al found that allele C was a risk factor for endometrial cancer risk, which may be due to the population diversity (Ashton et al, 2009). Wang et al found that the variant was associated with a protective effect on breast cancer (Wang et al, 2007); however, a meta-analysis suggested no correlation for the variant and breast cancer risk was found (Li et al, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…Synonymous mutations have been postulated to influence gene transcription through several means (Setiawan et al, 2004): the local concentration of transfer RNA varies for different codons; the mutation on messenger RNA (mRNA) may induce the formation of hairpins and result in mRNA instability or transcriptional inactivity; or the polymorphism gives rise to linkage disequilibrium with the other site mutation, such as the polymorphism on the ER-β gene 5ꞌG1082A and 3ꞌ untranslated region A1730G, which cross-links with the polymorphism on the splicing site of the 8th exon and affects the splicing of the 8th exon. Additionally, the polymorphism can induce an alteration in the secondary structure of ER-β mRNA and lead to changes at the mRNA level, affecting synthesis, splicing, maturation, translocation, translation, and degradation, among other processes (Aschim et al, 2005;Ashton et al, 2009;Safarinejad et al, 2010).…”
Section: Discussionmentioning
confidence: 99%